Teacher Performance: The effect on Teacher Satisfaction in Public Senior High Schools - Hamidi Hamidi; A. Wahab Jufri; I Wayan Karta (Postgraduate, University of Mataram, 2021)
This research aim to determine the effect of performance on teachers satisfaction in Public Senior High Schools in Lombok, Indonesia. This study is a quantitative study was conducted in Lombok with a population of 580 teachers. The total sample of 85 teachers was obtained by a proportional random sampling technique. Data analysis was performed by regression. The results showed that performance has an impact on teacher satisfaction. The teachers of public senior high school in Lombok will be satisfied if their performance is very good. It was concluded that one way to maintain teacher satisfaction is by improving performance